Myelodysplastic Syndrome with Myelofibrosis Transformed to a Precursor B-Cell Acute Lymphoblastic Leukemia: A Case Report with Review of the Literature - Ayed A. Algarni; Mojtaba Akhtari; Kai Fu (Case Reports in Hematology)
Myelodysplastic syndromes (MDS) comprise a group of heterogeneous clonal hematopoietic cell disorders characterized by cytopenias, bone marrow hypercellularity, and increased risk of transformation to acute leukemias. MDS usually transformed to acute myeloid leukemia, and transformation to acute lymphoblastic leukemia (ALL) is rare. Herein, we report a unique patient who presented with MDS with myelofibrosis. Two months after the initial diagnosis, she progressed to a precursor B-cell acute lymphoblastic leukemia. She was treated with induction therapy followed by allogenic stem cell transplantation. She was alive and doing well upon last followup. We have also reviewed the literature and discussed the clinicopathologic features of 36 MDS patients who progressed to ALL reported in the literature.